Memorandum on first steps towards the improvement of the general medical services of the nation (London : Council of the Medical Practioners' Union, 1939)
1939 1939 1930s 6 pages 4 (5) The first steps towards the improvement of our general medical services to which the Union now calls the attention of the public and the medical profession are :— (а) The extension of general practitioner services to the whole population. (b) The removal of the pauper taint from all forms of medical service. (c) The correction of grave defects in recent maternity legislation. (d) The radical improvement of medical education. 2. EXTENSION OF GENERAL PRACTITIONER SERVICES TO ALL. (6) The Union believes that it is much more important to bring general practitioner services within reach of the dependants of the insured than it is to provide specialist and institutional services. These latter are widely available even now, and existing legislation permits County and Borough Councils to make such further provision under both heads as may be required. These Councils must fill up the gaps until their services can, in due course, be incorporated in a national system. (7) The existing general practitioner system makes no provision, except only perhaps for the indigent poor, for looking after patients who cannot themselves afford any sort of fee. There are not wanting critics who declare that the doctors themselves should provide for these patients who cannot make any payment for medical services, instead of leaving it to the State to do. When they are asked why, no reasonable explanation is forthcoming. The State and the community hardly expect to get such services for nothing. General practitioners have a wonderful record of charitable service, but compulsory charity is certainly unfair when applied to one section of citizens alone. (8) By far the simplest method open to the State is to make use of existing practitioners, who alone know the work, and to impose upon them at first no more radical changes than are essential. In other words, the probability is that, in the first instance, the benefits of the Panel system, and only those benefits, will be extended to a wider sphere. This will be done for motives of expediency, and not with any particular desire to continue any one system or to support any political theory. (9) There are two points with regard to this extension upon which it would be well if purely political interests could be faced with a measure of agreement between the contending interests. The first is whether the extension of service is to include the whole community or to operate under an income limit only. The second is whether the doctor is to be paid wholly by way of a fixed salary, or by a variable remuneration according to the number of patients treated as under the present Panel system. (10) On these points the Medical Practitioners' Union long ago announced its policy and has seen no cause to vary it. That the policy may need to be varied as the service develops, or in case of war or national emergency, is well recognised by the Union. Its present policy is a policy for the present and not one which cannot be adapted to such new circumstances as may arise. (11) The Union believes that the general practitioner service should be extended to the whole population without distinction of wealth or class. It has not adopted this view because it adheres to any political or economic theory, but because it seems a needless expense and complication to set up machinery whereby a small section of comparatively wealthy persons should be excluded from benefits of which in any case they will probably not wish to avail themselves. Nor is it at all obvious that such machinery could be devised without introducing more anomalies and difficulties than it could hope to remedy. The only people who would have cause to complain of this arrangement would be those practitioners whose income is derived chiefly from the well-to-do classes. It might be found that the State had done them a considerable injustice and this would have to be remedied, as it could be. That a problem of this sort would need consideration and solution is no argument against the introduction of a system otherwise convenient and administratively simple, although the medical profession could not be expected to agree until guarantees had been provided that no one's living would be taken away from him. (12) The Union is opposed to the continuance of insurance contributions in respect of medical benefits. The charge for medical benefit should be upon the State, and not upon the individual. Contributions for sickness and unemployment benefit present problems outside the scope of this Memorandum. (13) The Union is further of the opinion that the remuneration of the practitioner should proceed upon the present basis, that is, that each patient treated should produce a 36/H24/38